2015
DOI: 10.1007/s40684-015-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal workpiece orientation to reduce the energy consumption of a milling process

Abstract: Rank JIF (%) Mechanical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Machining systems, as some of the most important and widespread subsystems in manufacturing [8], play a key role in energy-saving for the manufacturing industry [9]. Moreover, a study conducted by Gutowski showed a very interesting result [10]: CO 2 emissions of one computer numerical control (CNC) machine tool (22 kW spindle power) in one year are equivalent to the CO 2 emissions of 61 SUVs (20.7 mpg, 12,000 miles/year).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Machining systems, as some of the most important and widespread subsystems in manufacturing [8], play a key role in energy-saving for the manufacturing industry [9]. Moreover, a study conducted by Gutowski showed a very interesting result [10]: CO 2 emissions of one computer numerical control (CNC) machine tool (22 kW spindle power) in one year are equivalent to the CO 2 emissions of 61 SUVs (20.7 mpg, 12,000 miles/year).…”
Section: Figurementioning
confidence: 99%
“…Turning, milling, drilling and grinding processes are widely used in the manufacturing industry [8]. Unfortunately, a large number of existing studies have shown that the energy efficiencies of the above machining processes are generally less than 30% [11][12][13]34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…14,18 And in this study, the results of the effects of the various machining parameters on MRR of the AEDM-HS process were obtained through orthogonal analysis. The analysis examined the pulse duration, working current and duty cycle, whereas the applied voltage and the tool electrode rotation speed were fixed at 80V and 15000 rpm respectively.…”
Section: Orthogonal Experiments On Mrrmentioning
confidence: 99%
“…Thus, the reduction of energy consumption in the manufacturing field is required. From this point of view, the energy consumption in manufacturing systems and machine tools has been measured and investigated by many researchers [1][2][3][4][5][6][7]. For example, Lee et al [3] developed an energy model of a machine tool and estimated the total energy consumption of variable machine tools by decoupling the cutting power.…”
Section: Introductionmentioning
confidence: 99%